Feasibility of Concussion Rehabilitation Approaches Tailored to Psychological Coping Styles: A Randomized Controlled Trial - Silverberg, Noah D; Cairncross, Molly; Brasher, Penelope M A; Vranceanu, Ana-Maria; Snell, Deborah L; Yeates, Keith Owen; Panenka, William J; Iverson, Grant L; Debert, Chantel T; Bayley, Mark T; Hunt, Cindy; Baker, Andrew; et al. (Archives of physical medicine and rehabilitation, 2022)
To evaluate the feasibility of a clinical trial involving participants with concussion randomized to treatments designed to address fear avoidance or endurance coping, which are risk factors for disability. A secondary objective was to evaluate whether each treatment could affect selective change on targeted coping outcomes. Randomized controlled trial. Outpatient concussion clinics. Adults (N=73, mean age=42.5y) who had persistent postconcussion symptoms and high avoidance or endurance behavior were enrolled at a mean of 12.9 weeks post injury. Ten participants did not complete treatment. Participants were randomized to an interdisciplinary rehabilitation program delivered via videoconferencing and tailored to avoidance coping (graded exposure therapy [GET]) or endurance coping (operant condition-based pacing strategies plus mindfulness training [Pacing+]). Feasibility outcomes included screening efficiency, accrual, credibility, treatment fidelity, adherence, and retention. Avoidance was measured with the Fear Avoidance Behavior after Traumatic Brain Injury Questionnaire and endurance behavior with the Behavioral Response to Illness Questionnaire. Screening efficiency, or the proportion of clinic patients who were assessed for eligibility, was 44.5% (275 of 618). A total of 65.8% (73 of 111) of eligible patients were randomized (37 to GET, 36 to Pacing+), meeting accrual targets; 91.7% (55 of 60) of participants perceived treatment as credible. Therapists covered a mean of 96.8% of essential prescribed elements, indicating excellent fidelity. The majority (71.2%; 47 of 66) of participants consistently attended treatment sessions and completed between-session homework. Retention was strong, with 65 of 73 (89%) randomized participants completing the outcome assessment. GET was associated with greater posttreatment reductions in avoidance behavior compared with Pacing+ (Cohen's d , 0.81), whereas the treatment approach-specific effect of Pacing+ on endurance behavior was less pronounced (Cohen's d , 0.39). These findings support a future efficacy-focused clinical trial. GET has the potential to selectively reduce fear avoidance behavior after concussion, and, via this mechanism, to prevent or reduce disability.